The Tuberculosis Sentinel Research Network (TB-SRN) of the International epidemiology Databases to Evaluate AIDS (IeDEA): protocol for a prospective cohort study in Africa, Southeast Asia and Latin America - Eugene Messou; Marcel Yotebieng; Lukas Fenner; Helen Byakwaga; Stephany N Duda; Kara Wools-Kaloustian; Marie Ballif; Timothy R Sterling; Denise Evans; Annette H Sohn; Carolyn Bolton-Moore; Armel Poda; et al. (BMJ Open)
Introduction Tuberculosis (TB) is a leading infectious cause of death globally. It is the most common opportunistic infection in people living with HIV, and the most common cause of their morbidity and mortality. Following TB treatment, surviving individuals may be at risk for post-TB lung disease. The TB Sentinel Research Network (TB-SRN) provides a platform for coordinated observational TB research within the International epidemiology Databases to Evaluate AIDS (IeDEA) consortium.Methods and analysis This prospective, observational cohort study will assess treatment and post-treatment outcomes of pulmonary TB (microbiologically confirmed or clinically diagnosed) among 2600 people aged ≥15 years, with and without HIV coinfection, consecutively enrolled at 16 sites in 11 countries, across 6 of IeDEA’s global regions. Data regarding clinical and sociodemographic factors, mental health, health-related quality of life, pulmonary function, and laboratory and radiographic findings will be collected using standardised questionnaires and data collection tools, beginning from the initiation of TB treatment and through 12 months after the end of treatment. Data will be aggregated for proposed analyses.Ethics and dissemination Ethics approval was obtained at all implementing study sites, including the Vanderbilt University Medical Center Human Research Protections Programme. Participants will provide informed consent; for minors, this includes both adolescent assent and the consent of their parent or primary caregiver. Protections for vulnerable groups are included, in alignment with local standards and considerations at sites. Procedures for requesting use and analysis of TB-SRN data are publicly available. Findings from TB-SRN analyses will be shared with national TB programmes to inform TB programming and policy, and disseminated at regional and global conferences and other venues.